Initier des élèves de 4-5 ans à la géographie : enjeux et défis - Alain Pache; Béatrice Rogéré Pignolet; Anne-Sophie Gavin (Recherches en Éducation)
This article looks at the issues involved in teaching geography in Cycle 1 and the results of collaborative research into teaching practices. In French-speaking Switzerland, geography teaching underwent major shifts with the introduction of the Plan d’Études Romand. For teachers, implementing this new curriculum and the investigative approach proposed by the official teaching resources is proving complicated. The collaborative research system enabled one teacher to be coached in the construction of a teaching sequence based on geographical questioning, the subject of which was the playground. The teaching of spatial issues from a scientific geography requires ongoing training to promote professional development of generalist teachers.